A genome-wide pleiotropy scan for prostate cancer risk - Panagiotou, Orestis A.; Travis, Ruth C.; Campa, Daniele; Berndt, Sonja I.; Lindstrom, Sara; Kraft, Peter; Schumacher, Fredrick R.; Siddiq, Afshan; Papatheodorou, Stefania; Stanford, Janet L.; Albanes, Demetrius; Virtamo, Jarmo R K; et al. (My University, 2015)
Background No single-nucleotide polymorphisms (SNPs) specific for aggressive prostate cancer have been identified in genome-wide association studies (GWAS). Objective To test if SNPs associated with other traits may also affect the risk of aggressive prostate cancer. Design, setting, and participants SNPs implicated in any phenotype other than prostate cancer (p ≤ 10-7) were identified through the catalog of published GWAS and tested in 2891 aggressive prostate cancer cases and 4592 controls from the Breast and Prostate Cancer Cohort Consortium (BPC3). The 40 most significant SNPs were followed up in 4872 aggressive prostate cancer cases and 24 534 controls from the Prostate Cancer Association Group to Investigate Cancer Associated Alterations in the Genome (PRACTICAL) consortium. Outcome measurements and statistical analysis Odds ratios (ORs) and 95% confidence intervals (CIs) for aggressive prostate cancer were estimated. Results and limitations A total of 4666 SNPs were evaluated by the BPC3. Two signals were seen in regions already reported for prostate cancer risk. rs7014346 at 8q24.21 was marginally associated with aggressive prostate cancer in the BPC3 trial (p = 1.6 × 10-6), whereas after meta-analysis by PRACTICAL the summary OR was 1.21 (95% CI 1.16-1.27; p = 3.22 × 10-18). rs9900242 at 17q24.3 was also marginally associated with aggressive disease in the meta-analysis (OR 0.90, 95% CI 0.86-0.94; p = 2.5 × 10-6). Neither of these SNPs remained statistically significant when conditioning on correlated known prostate cancer SNPs. The meta-analysis by BPC3 and PRACTICAL identified a third promising signal, marked by rs16844874 at 2q34, independent of known prostate cancer loci (OR 1.12, 95% CI 1.06-1.19; p = 4.67 × 10;bsupesup it has been shown that SNPs correlated with this signal affect glycine concentrations. The main limitation is the heterogeneity in the definition of aggressive prostate cancer between BPC3 and PRACTICAL. Conclusions We did not identify new SNPs for aggressive prostate cancer. However, rs16844874 may provide preliminary genetic evidence on the role of the glycine pathway in prostate cancer etiology. Patient summary We evaluated whether genetic variants associated with several traits are linked to the risk of aggressive prostate cancer. No new such variants were identified.
Keywords: Aggressive prostate cancer; Genome-wide association study; Glycine; Pleiotropy; Single-nucleotide polymorphism